Pengaruh Komisaris Independen, Karakter Eksekutif, Profitabiltas dan Ukuran Perusahaan terhadap Tax Avoidance - Tagor Darius Sidauruk; Nandini Trimelinia Pebriani Putri (Penerbit Goodwood, 2022)
Purpose: This study aims to determine the effect of independent commissioner, executive character, profitability and company size on tax avoidance. Method: The sample of this study uses mining sector companies listed on the indonesia stock exchange (IDX) for the period 2017-2020. The sample determination uses purposive sampling method, so that this study obtains a final sample of 44 companies. Result: This study finds that independent commissioner, profitability has a positive effect on tax avoidance and company size has a negative effect on tax avoidance. While the executive character has no effect on tax avoidance. Limitations: This study found that independent commissioners, executive character, profitability and company size can only affect tax avoidance by 37,4 percent. This condition indicates that there are other variables that can affect tax avoidance, but are not included in this study. In addition, this study is limited to using a sample of 44 companies in the mining sector listed on the IDX. Contribution: This research is expected to be able to increase knowledge about tax avoidance in Indonesia, and provide isight in detecting tax avoidance practices in the mining sector. This study also contributes to managerial implications, where tax avoidance actions taken must remain in accordance with applicable regulations.